The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
0 votes
49 views
Let f∘gf∘g denote function composition such that (f∘g)(x)=f(g(x))(f∘g)(x)=f(g(x)). Let f:A→Bf:A→B such that for all g:B→Ag:B→A and h:B→Ah:B→A we have f∘g=f∘h⇒g=hf∘g=f∘h⇒g=h. Which of the following must be true?

Ans: One-one.

My doubt: WHY IT IS NOT ONTO ?
asked in Set Theory & Algebra by (237 points) | 49 views

Please log in or register to answer this question.

Related questions

0 votes
0 answers
5
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
49,808 questions
54,481 answers
188,251 comments
74,530 users